Signifying the End of Swidden? An Analysis of Vocabulary of the Fallow Stage Among a Kalimantan Indigenous Group, Indonesia (Forest and Society, 2025)
This study examines how the Dayak Tunjung community in East Kalimantan, Indonesia, employs linguistic classifications to structure and transmit ecological knowledge within a traditional swidden agricultural system. It focuses on the vocabulary used to denote fallow stages and analyzes how generational shifts in language use reflect broader socio-ecological transformations. Data were collected through 16 semi-structured interviews and participant observation in Linggang Melapeh Village, stratified by age and occupation to capture intergenerational dynamics. The findings reveal that older generations retain a detailed lexicon tied to ecological succession and customary land practices, while younger members increasingly adopt shortened fallow cycles and show a declining familiarity with traditional terms. These patterns indicate a process of biocultural erosion, wherein linguistic attrition parallels the restructuring of ecological relationships under the pressures of land commodification and shifting livelihood strategies. The study highlights the need to revitalize Indigenous ecological narratives and safeguard linguistic diversity as critical components of cultural and environmental sustainability. Furthermore, it calls for decolonizing conservation frameworks to recognize and empower Indigenous governance systems. Integrative efforts involving education, participatory mapping, and culturally grounded policy interventions are recommended to sustain the ecological and linguistic heritage of the Dayak Tunjung community.
Keywords: Ecolinguistics; Fallow vocabulary; Dayak Tunjung; Swidden agriculture; Biocultural erosion; East Kalimantan